Toulouse Lautrec syndrome: Report of a rare clinical entity - N, Benazir Banu; Manoharan, GV Murali Gopika; Bakyalakshmi, K (Indian Journal of Case Reports, 2024)
Pycnodysostosis, first described by Maroteaux and Lamy in the year 1962, is a rare autosomal recessive disorder. It is a lysosomal storage disease of the bone attributed to the mutation of the gene that is responsible for encoding the enzyme cathepsin K, thereby inhibiting the normal osteoclastic function, making the bones abnormally dense and brittle. We report a case of 30-year-old female herewith, who presented with characteristic features such as short stature, acro-osteolysis, open fontanelles, generalized osteosclerosis, and oral manifestations including grooved palate, malpositioned teeth with increased incidence of dental caries. There is an increased risk of mandibular fractures and osteomyelitis following invasive dental treatments. Thus, early diagnosis helps clinicians to manage patients with minimally invasive procedures preventing complications.